Effect of paddy winter submergence on invertebrate communities in a temperate rice cropping environment (Lomellina, NW Italy) - Tiziano Bo; Anna Marino; Elisa Falasco; Barbara Moretti; Lucia Crosetto; Daniel Said-Pullicino; Stefano Fenoglio (Paddy and Water Environment, 2026)
Rice fields are one of the most important and extensive agroecosystems in the world. In Europe, Italy is a major rice producer, with a significant proportion of the yield originating from a vast area within the Po Valley. In this study, we investigated the impact of adopting winter flooding (an established practice in Asia, but novel to Northern Italy) on the biodiversity, abundance, and functional organisation of aquatic invertebrate communities. In particular we attempt to: (i) describe and compare the biodiversity of aquatic invertebrates in the study area, (ii) assess how winter submergence affects the structural and functional composition of aquatic invertebrate communities (iii) provide recommendations to increase the sustainable management of rice fields. Preliminary results suggest that maintaining water in intensive agricultural areas during the cold season could serve as a substitute for lost natural wetlands and enhance local biological and functional diversity. Indeed, although our study pointed out that winter flooding does not lead to a significant increase in the richness and abundance of invertebrate communities, this practice can be potentially useful since flooded rice fields host a community that would otherwise disappear and which plays an important role in both spring recolonization and organic matter decomposition.

Grassland duration affects soil organic carbon pools only in the topsoil and has limited effects on microbial metabolism - Claudia Dămătîrcă; Barbara Moretti; Laura Zavattaro; Julia Schroeder; Christopher Poeplau; Alexandra Ciorîţă; Marco Pittarello; Luisella Celi; Giampiero Lombardi (Agriculture, Ecosystems & Environment, 2025)

Factors influencing nitrogen derived from soil organic matter mineralisation: Results from a long-term experiment - Octavian P. Chiriac; Marco Pittarello; Barbara Moretti; Laura Zavattaro (Agriculture, Ecosystems & Environment, 2025)

Evaluation of attenuated Salmonella Typhimurium (STMΔznuABC) anticancer activity on canine mammary cancer-associated fibroblasts - Barbara Chirullo; Floriana Fruscione; Genny Del Zotto; Filippo Dell'Anno; Michela Tarantino; Ilaria Porcellato; Paola Petrucci; Chiara Grazia De Ciucis; Antonello Bufalari; Lisa Guardone; Katia Cappelli; Giulia Moretti; et al. (Research in Veterinary Science, 2024)

The environmental and agronomic benefits and trade-offs linked with the adoption alternate wetting and drying in temperate rice paddies - Andrea Vitali; Barbara Moretti; Chiara Bertora; Eleonora Francesca Miniotti; Daniele Tenni; Marco Romani; Arianna Facchi; Maria Martin; Silvia Fogliatto; Francesco Vidotto; Luisella Celi; Daniel Said-Pullicino (Field Crops Research, 2024)

Interaction between water, crop residue and fertilization management on the source-differentiated nitrogen uptake by rice - Andrea Vitali; Federica Russo; Barbara Moretti; Marco Romani; Francesco Vidotto; Silvia Fogliatto; Luisella Celi; Daniel Said-Pullicino (Biology and Fertility of Soils, 2024)
Alternate wetting and drying (AWD) is an effective water-saving practice for rice cultivation that may however promote nitrogen (N) losses compared to continuous flooding (CF). The interaction between water, crop residue and N fertilization management can influence the contribution of different N sources to plant uptake. We hypothesized that microbial processes driving the source-differentiated N supply for rice uptake during the early growth stages will depend on the interaction between water management, the timing of straw incorporation with respect to flooding and the temporal distribution of mineral N application. Rice was grown for 60 days in mesocosm experiment involving a factorial design with (i) two water regimes (CF vs. AWD) and (ii) three straw and fertilizer managements, during which soil N, porewater chemistry, plant growth and N uptake were evaluated. Source partitioning of plant N between fertilizer-, straw- and soil-derived N was achieved by means of a dual-stable isotope 15 N tracing approach. Although AWD reduced total N uptake by about 4–25% with respect to CF, this could only be partly attributed to a lower uptake of fertilizer-N (and lower fertilizer-N use efficiency), suggesting that other N sources were affected by water management. Our findings evidence how the interaction between soil redox conditions and the availability of labile C and inorganic N strongly determined the supply of soil-derived N through microbial feedback and priming responses. Although incorporated straw contributed only minimally to rice N, it represented the primary driver controlling plant N nutrition through these microbial responses. These insights may contribute to identify suitable fertilization practices that favour plant N uptake during the early stages of rice growth under AWD.

Conservation tillage in temperate rice cropping systems: Crop production and soil fertility - Andrea Vitali; Barbara Moretti; Cristina Lerda; Daniel Said-Pullicino; Luisella Celi; Marco Romani; Silvia Fogliatto; Francesco Vidotto (Field Crops Research, 2024)

Does association with N-fixing nurse trees improve carbon sequestration in walnut plantations? Case-study on a reclaimed opencast mine in Italy - Giacomo Certini; Maria Chiara Manetti; Barbara Mariotti; Alberto Maltoni; Gabriele Moretti; Francesco Pelleri (Forest Ecology and Management, 2023)

Residue incorporation and organic fertilisation improve carbon and nitrogen turnover and stabilisation in maize monocropping - Claudia Dămătîrcă; Barbara Moretti; Chiara Bertora; Andrea Ferrarini; Cristina Lerda; Ilaria Mania; Luisella Celi; Roberta Gorra; Laura Zavattaro (Agriculture, Ecosystems & Environment, 2023)

New insights into pathogenesis point to HIV-1 Tat as a key vaccine target - Barbara Ensoli; Sonia Moretti; Alessandra Borsetti; Maria Teresa Maggiorella; Stefano Buttò; Orietta Picconi; Antonella Tripiciano; Cecilia Sgadari; Paolo Monini; Aurelio Cafaro (Archives of Virology, 2021)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Occurrence of deoxynivalenol in an elderly cohort in the UK: a biomonitoring approach - Maria Papageorgiou; Liz Wells; Courtney Williams; Kay L.M. White; Barbara De Santis; Yunru Liu; Francesca Debegnach; Brunella Miano; Giorgio Moretti; Stephanie Greetham; Carlo Brera; Stephen L. Atkin; et al. (Food Additives & Contaminants: Part A, 2018)